Ethnomathematics in Javanese Death Commemoration: Etnomatematika Pada Peringatan Kematian Masyarakat Jawa - Sari, Nurul Husnah Mustika; Fahmy, Ahmad Faridh Ricky (Quadratic: Journal of Innovation and Technology in Mathematics and Mathematics Education, 2022)
In Java, there is a tradition called death commemoration. In Javanese society, death commemoration consists of geblag (commemoration afther funeral), commemoration at 3rd day of the death, 40th day of the death, 100th day of the death, 1 year, 2 years, and 1000th day of the death. This was a descriptive research. It used ethnography method. The data was collected by interview, observation, and literature study. The result said that to decide the day and pasaran of death commemoration, it is need to use modulo concept. We used modulo 7 to decide the day, because there are seven days in a week and to decide the pasaran we used modulo 5 because there are five pasarans. It means that death commemoration tradition in Javanese society applied mathematical concept. Then, death commemoration tradition in Javanese is a part of ethnomathematics.